Cultural Challenges Faced by African Students at the Western University in Malaysia - Moyo, Terence (2009)
In this chapter I am going to introduce the research study (cultural challenges faced by African students at the Western University in Malaysia) and outline the topics covered in the research. This chapter also brings about what the research is intended to do, the topic of self in the study, what drew me to choose this particular research question.